A implantação de inovação social por organizações participantes da matriz do empreendedorismo social - Lencini, Carlos Artur dos Santos (Universidade do Vale do Rio dos Sinos, 2013)
The study of social innovation is based on the identification of opportunities and improvements to the individual’s life and its dissemination to society as a way to mitigate the social imbalance. The organization and social entrepreneur play a preponderant role in the process of implementing social innovation. With this focus, this study brings the social entrepreneurship array as background to understand the interaction between entrepreneur and organization. This research aims at analyzing different types of organizations implementing social innovation and the motivations of entrepreneurs and its impacts. The theoretical presents the evolution of the concept and focus of the study of social innovation, social entrepreneurship and its characteristics, social organization and approach on the social entrepreneurship matrix. The research is classified as descriptive and qualitative. We have conducted interviews with entrepreneurs and beneficiaries. We have used a semi-structured guide. It contains open questions which are related to entrepreneurial characteristics, motivation, challenges, future prospects and social benefits. Data analysis consists of content analysis and relationship between categories. The results indicated that organizations have distinct characteristics identified by the social entrepreneurship array. We have had difficulty to properly classify the characteristics in the social entrepreneurship matrix. The motivations of entrepreneurs are related to family background, social vision and personal fulfillment participate in social transformation that occurs in the individual life or in the community. The impacts of social innovation are clear and transparent to beneficiaries. The result of impacts improved quality of life. These results are expressed in individual, family and organizational selfsufficiency.
Keywords: Empreendedorismo social; Impacto social; Inovação social; Matriz do empreendedorismo social; Negócio social; Organização social; Social business; Social entrepreneurship; Social business matrix; Social impact; Social innovation; Social organization; ACCNPQ::Ciências Sociais Aplicadas::Administração